Design of wideband power amplifier for gan hemt for radio application / Lim Wen Jun - Lim, Wen Jun (2017)
In the field of communication, the vast developing of the communication system in past decades that changes the way of interaction between mankind. In this thesis, the focus has been given to the design of single system where it can operate at wideband frequency in simplest circuit and enhanced performances. In this project, a wideband power amplifier (PA) is designed using real frequency technique (RFT). The motivation of this project is to show that by using the idea of RFT and practical implementation of distributed elements and lumped elements (mixed-lumped elements design), the PA designed is able to achieve satisfying results with wide bandwidth range of 80 MHz to 2200 MHz. The measurement results reported good performance over the bandwidth of the interest (i.e. power of 41 dBm, efficiency about 67% and gain more than 13 dB), and reasonable agreement with the simulated data. The results are significant for single-ended GaN HEMT device for the wideband operation starting from low frequency 80 –2200 MHz.